Leveraging the tolerogenic potential of TNF-α and regulatory B cells in organ transplantation - Poznansky, Sonya A.; Yu, Matthew; Deng, Kevin; Fu, Qiang; Markmann, James F.; LeGuern, Christian (Frontiers in Immunology, 2023)
A subset of B-cells with tolerogenic functions, termed B-regulatory cells or Bregs, is characterized by the expression of anti-inflammatory/tolerogenic cytokines, namely IL-10, TGF-β, and IL-35, that contribute to their regulatory functions. Breg regulation favors graft acceptance within a tolerogenic milieu. However, Bregs’ have also been shown to express other cytokines, including tumor necrosis factor-alpha (TNF-α), that show dual functions: promote or repress inflammation. As organ transplantation invariably triggers inflammation, new insights into the crosstalk between cytokines with dual properties and the inflamed milieu are needed to tailor their function toward tolerance. Using TNF-α as a proxy of dual-function cytokines involved in immune-related diseases and transplantation settings, the current review highlights the multifaceted role of TNF-α. It focuses on therapeutic approaches that have revealed the complexity of TNF-α properties tested in clinical settings where total TNF-α inhibition has proven ineffective and often detrimental to clinical outcomes. To improve the efficacy of current TNF-α inhibiting therapeutics, we propose a three-prong strategy to upregulate the tolerogenic pathway engaging the TNFR2 receptor while simultaneously inhibiting the inflammatory mechanisms associated with TNFR1 engagement. When combined with additional administrations of Bregs-TLR that activate Tregs, this approach may become a potential therapeutic in overcoming transplant rejection and promoting graft tolerance.